Extraordinary COVID-19 social support programs in South Africa yield economic benefits during the pandemic period - Gabriel, Sherwin; van Seventer, Dirk; Arndt, Channing; Davies, Robert J.; Harris, Laurence; Robinson, Sherman; Wilf, Jenna (International Food Policy Research Institute, 2022)
Since the onset of economic downturns caused by the COVID-19 pandemic, many countries have struggled with uneven recoveries across sectors, as some types of workers and industries were better able to resume their activities than others. Even in the best-case scenarios, recovery would have been precarious, but the spread of new virus variants has cast doubt on the hopes for rapid reopening and recovery, especially for low- and middle-income countries with low vaccination rates.